The Measurement of Spatial Competition: Evidence from the Real Estate Market - Ralph Siebert; Xiaoyan Zhou (CESifo GmbH, 2024)
This study provides a test for measurement of spatial competition in residential real estate markets. Several alternative spatial competition measures are tested. We employ a Bertrand oligopoly model with differentiated products and adopt a Spatial Autoregressive model using a two stage least squares estimator. Our results show that commonly used count-based measures using the number of competitors in specific geographic radii are outperformed by price-based measures using prices of nearest competing neighbors. The main reason is that the latter measure accounts for heterogeneous neighborhood density of competitors. The measure captures the decaying pattern of spatial price competition over distance. The measure also stands out in capturing het-erogeneous spatial price competition effects. We find that spatial price competition is more intense among high-value homes within the five nearest competing houses.
Keywords: D40; R10; R30; 330; price effects; real estate market; spatial competition; spatial econometrics; spatial markets